2021
DOI: 10.31234/osf.io/7gja2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social prevalence information is rationally integrated in belief updating

Abstract: People rely heavily on information from the social world to inform their real-world beliefs. We ask whether the perceived prevalence of a belief, divorced from any direct evidence, serves as an independent cue in belief updating. Using real-world pseudoscientific and conspiratorial claims, our experiment (N = 403 American adults) shows that increases in people’s estimates of the prevalence of a belief led to increases in their endorsement of said belief. Belief change was most dramatic when initial beliefs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…Participants who were already confident that their assessment of the PSC was correct were less likely to integrate the consensus message. This is in line with previous research, suggesting that high confidence in prior beliefs leads to belief perseverance (Pintrich et al, 1993;Savion, 2009) and lower confidence leads to a higher willingness to adjust prior beliefs (Orticio et al, 2021). Given that people with anti-consensus scientific beliefs are prone to be more overconfident regarding their knowledge (Light et al, 2022), our finding is of high relevance as it shows that even though consensus messages can correct false prior knowledge or beliefs unwarranted confidence in prior knowledge limits its effectiveness.…”
Section: Updating Psc: Confidence In Perceived Scientific Consensus A...supporting
confidence: 91%
See 1 more Smart Citation
“…Participants who were already confident that their assessment of the PSC was correct were less likely to integrate the consensus message. This is in line with previous research, suggesting that high confidence in prior beliefs leads to belief perseverance (Pintrich et al, 1993;Savion, 2009) and lower confidence leads to a higher willingness to adjust prior beliefs (Orticio et al, 2021). Given that people with anti-consensus scientific beliefs are prone to be more overconfident regarding their knowledge (Light et al, 2022), our finding is of high relevance as it shows that even though consensus messages can correct false prior knowledge or beliefs unwarranted confidence in prior knowledge limits its effectiveness.…”
Section: Updating Psc: Confidence In Perceived Scientific Consensus A...supporting
confidence: 91%
“…Unwarranted (over-)confidence in one's belief decreases the likelihood of changing that belief even if contradicting information is presented (Pintrich et al, 1993;Savion, 2009). On the other hand, recent research has shown that uncertainty about the beliefs one holds makes one more likely to change those beliefs in case of new information (Orticio et al, 2021). Thus, we propose that confidence in perceived scientific consensus should also predict evidence integration in the consensus messaging process.…”
mentioning
confidence: 86%
“…As has been shown in previous research, confidence might play an important role in whether or not new information is integrated into a set belief-or knowledge system (Dole & Sinatra, 1998;Heckerman & Jimison, 2013;Orticio et al, 2021;Pintrich et al, 1993;Savion, 2009). In their research Said, Frauhammer et al (2023) presented people with a message about the percentage of scientists agreeing that climate change was man-made.…”
mentioning
confidence: 80%